Hereditary spastic paraplegia (SPG 48) with deafness and azoospermia: A case report - Jin, Ping; Wang, Yu; Nian, Na; Wang, Gong-Qiang; Fu, Xiao-Ming (Frontiers in Neurology, 2023)
Hereditary spastic paraplegias (HSP) are inherited neurodegenerative disorders characterized by progressive paraplegia and spasticity in the lower limbs. SPG48 represents a rare genotype characterized by mutations in AP5Z1, a gene playing a role in intracellular membrane trafficking. This study describes a case of a 53-year-old male patient with SPG48 presenting spastic paraplegia, infertility, hearing impairment, cognitive abnormalities and peripheral neuropathy. The Sanger sequencing revealed a homozygous deletion in the chr 7:4785904-4786677 region causing a premature stop codon in exon 10. The patient's brother was heterozygous for the mutation. The brain magnetic resonance imaging found a mild brain atrophy and white matter lesions. In the analysis of the auditory thresholds, we found a significant hearing decrease in both ears.